LINGUOCULTURAL CHARACTERISTICS OF PRECEDENT UNITS IN MODERN LINGUISTICS - Bektoshev Otabek Kodiraliyevich; Makhmudova Saida; S. M. Makhmudova (Galaxy International Interdisciplinary Research Journal, 2022)
Each new member of the language tries to see the world not as a result of his own thinking, as a result of tests, but through the experiences instilled in the concepts of the language by his ancestors. Language is a phenomenon closely related to the world around us and the culture specific to each nation. The precedent units studied in this article occupy the main place in the field of lingvoculturology. The study of precedent units also plays an important role in elucidating aspects specific to language and culture. In our article, the analysis of the scientific research conducted on this term and its place in the field of linguistics are highlighted.